+0  
 
0
100
1
avatar

Solve for y if 9^y = 3^6

 

\(\phantom{27 27^4 81 81^2 81^3 81^4}\)

 

\(\phantom{1^2 + 2^2 + \dots + n^2}\)

 Jul 1, 2022

Best Answer 

 #1
avatar+2448 
0

Simplify the left-hand side: \({3^2}^y = 3^{2y}\)

 

Note that the exponents have the same bases, so we have \(2y = 6\)

 

Now, just solve for y. 

 Jul 1, 2022
 #1
avatar+2448 
0
Best Answer

Simplify the left-hand side: \({3^2}^y = 3^{2y}\)

 

Note that the exponents have the same bases, so we have \(2y = 6\)

 

Now, just solve for y. 

BuilderBoi Jul 1, 2022

21 Online Users